2013
DOI: 10.1016/j.immuni.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Lymph Node Fibroblastic Reticular Cells from Myofibroblastic Precursors Is Critical for Antiviral Immunity

Abstract: The stromal scaffold of the lymph node (LN) paracortex is built by fibroblastic reticular cells (FRCs). Conditional ablation of lymphotoxin-β receptor (LTβR) expression in LN FRCs and their mesenchymal progenitors in developing LNs revealed that LTβR-signaling in these cells was not essential for the formation of LNs. Although T cell zone reticular cells had lost podoplanin expression, they still formed a functional conduit system and showed enhanced expression of myofibroblastic markers. However, essential im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
321
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 220 publications
(353 citation statements)
references
References 50 publications
19
321
3
2
Order By: Relevance
“…BrdU-incorporating cells among the perivascular DN LNSC population (11) may generate new FRCs during viral infections, which is consistent with the dense accumulation of BrdU + FRCs around blood vessels that was observed in our longterm BrdU-labeling assay. The observation that increased FRC generation depends on LTbR is in line with a recent report by Ludewig and colleagues (11) showing that Ccl19 promoter-driven conditional ablation of LTbR eliminates mature FRCs but increases the fraction of DN LNSCs. An attractive hypothesis is that high levels of lymphotoxin expression by activated lymphocytes (27) triggers the differentiation of FRCs through direct interaction with intranodal FRC precursor cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…BrdU-incorporating cells among the perivascular DN LNSC population (11) may generate new FRCs during viral infections, which is consistent with the dense accumulation of BrdU + FRCs around blood vessels that was observed in our longterm BrdU-labeling assay. The observation that increased FRC generation depends on LTbR is in line with a recent report by Ludewig and colleagues (11) showing that Ccl19 promoter-driven conditional ablation of LTbR eliminates mature FRCs but increases the fraction of DN LNSCs. An attractive hypothesis is that high levels of lymphotoxin expression by activated lymphocytes (27) triggers the differentiation of FRCs through direct interaction with intranodal FRC precursor cells.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, there was a readily detectable proportion of proliferating cells within the LTbR + CD31 2 gp38 2 DN LNSC population in reactive PLNs (Supplemental Fig. 2C), which could contain FRC precursor cells (11). We also addressed whether FRCs might be replenished by circulating progenitors recruited to reactive LNs after viral infection.…”
Section: The Journal Of Immunologymentioning
confidence: 99%
“…Note added in proof. A recent study using Ccl19-cre conditional ablation of LTbR found that ERTR7 + networks are still formed in LNs in the absence of LTbR on FRC (50).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our understanding of whether FRCs similarly regulate the retention in the LNs of activated T cells is even less complete. That FRCs participate in an active immune response is suggested by the transcriptional changes that they exhibit in response to inflammation (8), the role of stromal-derived retinoic acid in promoting expression of gut-homing integrins by T cells (9), and by the proposal that their "maturation" may be required for the generation of antiviral immune responses (10). Recent studies have also suggested that LN FRCs suppress T-cell proliferation through their expression of Nos2 in response to T-cell-derived interferon (IFN)-γ (11-13).…”
mentioning
confidence: 99%